2000
DOI: 10.1590/s1516-31802000000600007
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding training for health professionals and resultant changes in breastfeeding duration

Abstract: This randomized trial supports a growing body of evidence that training hospital health professionals in breastfeeding promotion and protection results in an increase in breastfeeding duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 8 publications
1
32
0
7
Order By: Relevance
“…Estudo realizado recentemente com mulheres trabalhadoras norte-americanas revelou que estratégias de ampliação de espaços para a prática da amamentação no ambiente de trabalho contribuíram significantemente para a maior duração do aleitamento materno 39 . Assim, tem sido fortalecida a estratégia da rede social de apoio ao aleitamento materno, em especial entre as mães trabalhadoras, por constituírem grupo de maior risco de oferecer precocemente alimentos diferentes do leite materno à criança 30,37,38,39,40 .…”
Section: Resultsunclassified
“…Estudo realizado recentemente com mulheres trabalhadoras norte-americanas revelou que estratégias de ampliação de espaços para a prática da amamentação no ambiente de trabalho contribuíram significantemente para a maior duração do aleitamento materno 39 . Assim, tem sido fortalecida a estratégia da rede social de apoio ao aleitamento materno, em especial entre as mães trabalhadoras, por constituírem grupo de maior risco de oferecer precocemente alimentos diferentes do leite materno à criança 30,37,38,39,40 .…”
Section: Resultsunclassified
“…In the context of implementing the BFHI in Italy, an educational program that increased the knowledge of hospital workers on breastfeeding practices improved the breastfeeding outcome of exclusive breastfeeding in the early postpartum period as well as full breastfeeding at 3 and 6 months (Cattaneo & Buzzetti, 2001). Also in Italy, Taddei, Westphal, Venancio, Bogus, and Souza (2000) reported that training improved exclusive breastfeeding by 29%, whereas full breastfeeding increased by 20%. In a French university hospital, the effectiveness of a 3-day training program for maternity ward professionals who worked with healthy term babies was studied in a before-and-after design with the finding that the mechanism of education increased the duration of any breastfeeding from 13-16 weeks (Vittoz, Labarere, Castell, Durand, & Pons, 2004).…”
Section: Short-term Objectivesmentioning
confidence: 98%
“…Counselling as a single intervention in the community or by health staff demonstrated lower effects on EBF, suggesting the importance of linking communities with health facilities to support EBF (76,78) . Strong implementation of the tenth step of the WHO/ UNICEF 10 Steps of Successful Breast-feeding is a key aspect of sustaining gains in breast-feeding achieved in maternity wards beyond the day of birth, evidenced by the lack of strong breast-feeding outcomes/benefits, often due to weak implementation and support at the community level (79,(86)(87)(88) . Targeted breast-feeding promotion and support by trained clinic personnel in tandem with peer-based counselling for addressing breast-feeding problems is needed.…”
Section: Promising Interventions and Programmatic Implications Of Thementioning
confidence: 99%